If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14q + 7 = 39 Reorder the terms: 7 + 14q = 39 Solving 7 + 14q = 39 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 14q = 39 + -7 Combine like terms: 7 + -7 = 0 0 + 14q = 39 + -7 14q = 39 + -7 Combine like terms: 39 + -7 = 32 14q = 32 Divide each side by '14'. q = 2.285714286 Simplifying q = 2.285714286
| -8-3x=8 | | -6=5t | | 3x+10-3=10 | | 2.1(4.6+1.3y)=10.68y+-18.32 | | 64=-8h | | Y=-16t^2+30t+64 | | 7a+10=2a+1 | | -8+3m=m | | 5-t+3t+2= | | S^2-s-3=a | | x/14+21=22 | | 4(6x+5)=3(8x+5) | | c-(-3)=-7 | | 2(9*9)= | | -7p(p+8)=21 | | 3x=x+4+48 | | 15*5*3x+3=-1*3*5*15 | | 4.9=2x+2.3 | | 3X-4(-3X-7)=13 | | (4r-2)=12 | | f-9=2 | | -(3z-4)= | | 3-2=2-5 | | 3y+5+2y-7=153 | | 3x+1=1x+13 | | 8x^2-12x-4=0 | | 5x^2=210x | | g-2y=9 | | y-12=-2x-2 | | -2y+x=9 | | 7-5x=-8(6+2x) | | -3x+10x= |